Manganese (Mn) Accumulation in Jerbung Shrimp (Penaues merguensis) from the Sungsang Estuary, South Sumatra - Liana, Anjar Puteri; Putri, Wike Ayu Eka; Melki, Melki; Barus, Beta Susanto; Fitri Agustriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Estuaries are intermediate environments that are extremely susceptible to pollution, especially heavy metals like manganese (Mn). The goals of this research were to determine the amount of manganese in the consumable flesh of Jerbung shrimp (Penaeus merguiensis) taken from the Sungsang Estuary in Banyuasin Regency, South Sumatra, Indonesia, and to ascertain the safe intake levels for people. Atomic Absorption Spectrophotometry (AAS) was used to analyze the shrimp samples at a wavelength of 257. 61 nm. According to the findings, the average Mn content in shrimp muscle was somewhat higher than the limit set by the European Food Safety Authority (EFSA), falling between 3. 16 and 3. 21 mg/kg. Even if just shrimp are consumed, the projected consumption limits based on dietary intake calculations still suggest a comparatively low immediate health risk. However, the high Mn concentration indicates the effect of environmental pollution brought about by human actions in the Musi River estuary. These findings emphasize the significance of controlling pollution sources and carrying out routine environmental monitoring to ensure the safety of seafood and the sustainability of estuarine ecosystems.